Effect of Moringa Oleifera Leaf Extract (Mole) on Some Reproductive Parameters of Rabbits Reared in a Semi-Humid Environment (Global Journal of Science Frontier Research, 2017)
This research was conducted at the Kwara State Teaching and Research farm University, Malete
Keywords: abnormal sperm cells; sperm concentration; testicular morphometry; moringa oleifera; testosterone